2013
DOI: 10.1002/ccd.24800
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in long‐term outcome after primary percutaneous intervention for ST‐segment elevation myocardial infarction

Abstract: Women have higher rates of both MACE and mortality after primary PCI for STEMI compared to men because of higher age with higher baseline risk profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 32 publications
8
54
1
2
Order By: Relevance
“…In our patient population, 1-year death occurred in one woman out of five. Some previous studies have reported lower event rates during follow-up [7,15], while other registries have reported similar results to ours at 1 year [10,16]. Sex and outcomes after STEMI PCI 7 This high rate may be explained by the unselected nature of our study population, without any patient exclusion, and the particularly high-risk profile (9.8% OHCA and 5.6% ECMO in men; 14.8% cardiogenic shock in women).…”
Section: Discussionsupporting
confidence: 65%
“…In our patient population, 1-year death occurred in one woman out of five. Some previous studies have reported lower event rates during follow-up [7,15], while other registries have reported similar results to ours at 1 year [10,16]. Sex and outcomes after STEMI PCI 7 This high rate may be explained by the unselected nature of our study population, without any patient exclusion, and the particularly high-risk profile (9.8% OHCA and 5.6% ECMO in men; 14.8% cardiogenic shock in women).…”
Section: Discussionsupporting
confidence: 65%
“…9,363,372 This may be related to higher rates of underlying hypertension, DM, and HF or may be due to longer delay in presentation to the hospital. 12,14,15,247,[365][366][367][368][369] Given the significant mortality benefit of early revascularization for patients with ACS, women with AMI-associated HF should undergo early angiography with subsequent risk stratification and revascularization when appropriate. 216,217,354 Medical stabilization with diuretics, vasodilators, inotropes, and percutaneous mechanical support should be provided when clinically indicated.…”
Section: Heart Failurementioning
confidence: 99%
“…7 Multiple studies have shown that women with acute coronary syndromes (ACS) are less likely to be treated with guideline-directed medical therapies, [8][9][10] less likely to undergo cardiac catheterization, [8][9][10][11] and less likely to receive timely reperfusion. 9,10,[12][13][14][15][16] Improving CHD morbidity and mortality and closing the knowledge gaps on AMI clinical presentations and treatments for women are public health priorities. This American Heart Association (AHA) scientific statement provides a comprehensive review of the current evidence of the epidemiology, clinical presentation, pathophysiology, treatment, and outcomes of women with AMI.…”
mentioning
confidence: 99%
“…102,190,191 Significant differences in the rate of reperfusion therapy between genders and hidden confounders such as frailty in elderly women with STEMI may have influenced their results. Recent observational studies including patients treated with PPCI 122,192,193 and pre-specified gender analysis of RCTs 126,127,132,189,194 have shown that the impact of gender on mortality could mainly be explained by differences in age and comorbidities between genders, in accordance with our results. On the contrary, another observational studiy and a meta-analysis have reported higher multivariable adjusted risk of early mortality in women with STEMI treated with PPCI.…”
Section: Association Between Gender and Risk For Short Term Mortalitysupporting
confidence: 91%
“…The age gap between genders in our population was substantially higher compared to previous studies, with a mean age difference of 10 years. 127,189 In spite of appropriate statistical methods that were used for adjustment, adjustment for such age-difference is awkward. Additionally, the age difference may indicate a selection bias.…”
Section: Association Between Gender and Risk For Short Term Mortalitymentioning
confidence: 99%